ETOS KERJA PENGUSAHA MUSLIM (Studi Kasus pada Pengusaha Muslim Alumni UIN Walisongo Semarang) - Huda, Choirul (Economica: Jurnal Ekonomi Islam, 2016)
This study focused on the work ethos of Moeslim entrepreneurs who graduated from UIN Walisongo Semarang. It is very interesting to study because of their profession as a businessmen and their educational background which based on Islamic sciences.Through a qualitative descriptive approach, there are two issues to be answered, namely how the work ethos of Muslim entrepreneurs who graduated from UIN Walisongo Semarang in running a business and how relationships between work ethos of muslim entrepreneurs with their success in business?Results of this study stated that Muslim entrepreneurs who graduated from UIN Walisongo Semarang have a high work ethic as capital in running and developing a business that was involved. Their work ethos is not only driven by economic motives, namely in order to meeth the economic needs alone, but it is also driven by social and religious motives. It correlates with the answer to the second issue, that, a high work ethich as been able to deliver the mon the success of the business that was involved, albeit with varying levels of success. It was determined by the type of business that is occupied and the time period to run the business. It also showed a good ability of the entrepreneur to manage and develop their business